تمثال کاری کی تحریک - Rehman, Dr. Tasneem (Zoraiz, 2023)
Images have always been used in the literature of almost all the languages yet there has been an immense increase in the tendency to create images in the Modern age. This emphasis on the use of images was due to the imagist movement launched by Ezra pound and his followers in 1912.It influenced the Urdu poets as well. The article in hand aims at finding out how this movement was motivated by Chinese and Japanese ancient poetry. It also enlightens its history, causes and objects to know how deeply it affected modern poetry.